Unleashing environmental performance: The impact of green entrepreneurial motivation on small enterprises - Al Shammre, Abdullah Sultan; Alshebami, Ali Saleh; Ali Seraj, Abdullah Hamoud; Elshaer, Ibrahim A.; Al Marri, Salem Handhal (Frontiers in Environmental Science, 2023)
Environmental degradation has been annoying, pressuring enterprises to look for innovative ways to improve their operations, methods and products. Accordingly, this research identifies the key factors contributing to developing innovative behaviour among small enterprises in Saudi Arabia and their effect on environmental performance (EP). The study collected a sample of 284 from different types of small enterprises operating in Saudi Arabia. The data collected were analysed using the partial least square structural equation modelling (PLS-SEM). The study revealed interesting results. It was found that green entrepreneurial motivation (GEM) can positively and significantly influence green innovation (GI) as well as environmental performance (EP). It was also found that GI can positively and significantly affect EP. Finally, GI could mediate the relationship between GEM and EP. Also, Knowledge sharing (KS) could moderate the relationship between GEM and GI. The study concluded by providing several recommendations for the policymakers in Saudi Arabia.